Multi-method approach effectively identifies and engages children impacted by parental substance misuse into school-based prevention services - Wood Merchant, Julie; Snell-Johns, Jessica (Frontiers in Public Health, 2024)
Children living in households where parents or caregiving adults misuse substances face significant risk academically, socially, physically, and emotionally. An estimated 12% or more of U.S. children lived with an adult with past-year substance use problems in 2009–2014. Engaging this high-need, underserved population in targeted prevention services is a public health imperative, requiring children first be identified. School-based services reduce access barriers and promote equitable access, providing a model that can address the scope and significance of parental substance misuse (PSM) on children. A review of published studies for this population revealed a lack of information regarding identification strategies and their relative effectiveness. This article uses data from a 2010–2020 field-based evaluation to analyze the performance of the Kids Like Us (KLU) program’s manualized approach to identifying and engaging elementary students impacted by PSM into its school-based program. KLU, a program of the Frederick County Health Department (Maryland, U.S.), is implemented in collaboration with public school counselors. KLU’s multi-method approach achieves universal prevention outcomes while simultaneously providing parent, self, school counselor, and community referral options. Over the 10-year study, 537 students were identified with a notable 83% of referred students completing 75–100% of sessions offered. Parent referral, a strategy not included in any reviewed studies, contributed the highest percentage of referrals (44% in response to a student take-home letter alone), followed by self (18%), school counselor (13%), and other/a combination (24%). KLU engaged students across varying school settings, sizes, and socioeconomics. Chi-square analysis of gender and ethnicity found no significant differences. Referral outcome and school counselor data results highlight the benefits of KLU’s multi-method, multi-source approach, including its ease of replication. KLU’s approach holds promise for addressing the public health crisis of children impacted by PSM. Study results highlight the need for policy changes including that U.S. and world alcohol and drug reports assess parent status. Additional research with a larger, more ethnically diverse population is recommended to examine the relationship between family and student demographics and referral strategies and sources.